Botswana : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Botswana. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper presents an overview of Botswana's economy. Botswana's diamond endowment-along with its track record of good macroeconomic policy management and political stability-contributed to high average economic growth and strong fiscal and balance-of-payments positions in recent years. Despite these achievements, Botswana faces unemployment, water and electricity shortages, and inefficiency of government operations. These challenges need to be addressed. Real GDP growth is estimated to be negative in 2015 owing to a decrease in global demand for diamonds and a deceleration of activity in the non-mining sector. However, the economy is expected to recover gradually in next three years driven by a gradual pick up in diamond prices and fiscal stimulus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet